Education on the utilization of artificial intelligence technology to support the development of learning media - Hidayati, Lina Nur; Rahmawaty, Penny; Mustaqim, Ilmawan; Ahmadi, Caesar Rosyad (Universitas Muhammadiyah Magelang, 2025)
The latest technological advancements that significantly impact human life today include Artificial Intelligence (AI). To support the learning process in the classroom, teachers' ability to utilize digital media is a crucial factor. This community service program aims to enhance teachers' skills in leveraging AI for the development of learning media. The methods used in this program include workshops, training, and mentoring. Evaluation results indicate that teachers have gained knowledge about the functions and benefits of various AI tools, such as ChatGPT, Gamma App, and Canva, in developing learning media. Furthermore, 77% of teachers stated that the program was highly beneficial, and 90% expressed high satisfaction with the educational program conducted.